Documents related to John Maynard Keynes, Institutionalism at Chicago & Frank H. Knight - Emmett, Ross B. (Research in the history of economic thought and methodology ;, 2013)
Research in the History of Economic Thought and Methodology is an annual research series which presents materials in two fields, both broadly considered: the history of economic thought and the methodology of economics.The annual A-volume contains peer-reviewed articles comparable to other academic journals in the history of economics, except that long pieces are welcome. The A-volume also publishes symposia, and review essays on new works in the history of economic thought, methodology and related fields (philosophy of science, sociology of science, rhetoric of science, and intellectual history), including multiple reviews of the same work.The annual B- and C-volumes are archival supplements that present previously unpublished materials -- lecture notes, papers, longer manuscripts, correspondence, etc.- of interest in both fields addressed in the A-vol.